Export of the outer membrane lipoprotein is defective in secD, secE, and secF mutants of Escherichia coli. - Sugai, M (1992)
The export of major outer membrane lipoprotein has been found to be affected in secD, secE, and secF mutants of Escherichia coli, which are defective in protein export in general. After a shift to the nonpermissive temperature, the kinetics of accumulation of prolipoprotein and pre-OmpA protein was indistinguishable from that of pre-OmpA protein accumulation in the secD and secF mutants but different in the secE mutant. The prolipoprotein accumulated in the secD, secE, and secF mutants at the nonpermissive temperature was not modified with glyceride. We conclude from these results and those of previous studies that the export of lipoprotein requires all common sec gene products except the SecB protein, i.e., the SecA, SecD, SecE, SecF, and SecY proteins.